Green energy - Victor Olteanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Strategic plans in the energy sector have the overall objective of the use of renewable energy, especially wind power, hydroelectricity, biomass intending a considerable increase in the share it has in total energy production. Thus, chase is moving towards an economy based on low carbon consumption and improve performance standards for the production, distribution and use of energy, helping to reduce greenhouse gas emissions, increase the use of renewable resources for energy production, to lower consumutilor. The aim of the study is to describe a few of production and technologies to reduce the consumption of energy in classical sources other than wind power and photovoltaic's.
Keywords: 330; renewable energy; pollution; ecological technologies